113k views
1 vote
Is x-4 equivalent to x3•x-7

User Jermane
by
4.3k points

2 Answers

6 votes

Answer:

YES

Explanation:


x^3\cdot x^(-7)=x^(3+(-7))=x^(-4)\\\\\text{used}\ a^n\cdot a^m=a^(n+m)\\\\\text{Other way}\\\\a^(-n)=(1)/(a^n)\\\\x^3\cdot x^(-7)=x^3\cdot(1)/(x^7)=(x^3)/(x^7)=(x\!\!\!\!\diagup^1\cdot x\!\!\!\!\diagup^1\cdot x\!\!\!\!\diagup^1)/(x\!\!\!\!\diagup_1\cdot x\!\!\!\!\diagup_1 \cdot x\!\!\!\!\diagup_1 \cdot x\cdot x\cdot x\cdot x)=(1)/(x^4)=x^(-4)

User Ben Harper
by
4.9k points
3 votes

Answer:

No.

Step-by-step explanation: Assuming you mean x^3*x-7, these two equations do not produce the same line.

User Uma Achanta
by
5.7k points